Hydra as an animal model system in Physiology - Alzugaray, Maria Eugenia (2021)
Hydra has been used as a model in different topics in biology, including physiology. It pertains to the Phylum Cnidaria, an ancestral group of Metazoa that shares a common ancestor with Bilateria. Hydra provides an experimental framework to analyze mechanisms that regulate the homeostasis and, due to the high level of gene conservation, can be easily extrapolated to other animal groups. We use this model to analyze physiological and evolutionary aspects of communication systems activated by food, and by the peptide messengers, Allatotropin (AT) and Allatostatin-C (AST-C). Using immunohistochemistry, quantum dots, bioinformatic, and physiological assays, we show that these systems are present in Hydra regulating feeding behavior. We analyze the regulation of the extrusion of the hypostome (that contains the mouth), showing that, whereas AT mimics the effect of the food, AST-C acts as antagonist. We show that those effects depend on changes in the cytosolic Ca2+ concentration, revealing the specific signaling pathway activated. Our data support the ancestral functions and conservation of these signaling systems that control myoregulatory activities related with feeding.